Consumer Rationality and Credit Cards - Brito, Dagobert L.; Hartley, Peter R. (Journal of Political Economy, 1995)
Borrowing on credit cards at high interest rates might appear irrational. However, even low transactions costs can make credit cards attractive relative to bank loans. Credit cards also provide liquidity services by allowing consumers to avoid some of the opportunity costs of holding money. The effect of alternative interest rates on the demand for card debits can explain why credit card interest rates only partially reflect changes in the cost of funds. Credit card interest rates that are inflexible relative to the cost of funds are not inconsistent with a competitive equilibrium that yields zero profits for the marginal entrant.